Plastic Management on the Kelapa Island, Indonesia: Analysis of Community Perception and Participation - Awaluddin Hidayat Ramli Inaku; Hadiyanto Hadiyanto; Henna Rya Abdurachim; Hashfi Hawali Abdul Matin (Universitas Diponegoro, 2023)
Plastic waste is a substance that is no longer used and contains certain elastic materials that require heat energy to decompose. Plastic waste has a longer time to decompose, which is about 20 to 100 years. The purpose of this study is to identify public perception and participation in plastic waste management, analyze the relationship between internal and external factors and perceptions of plastic waste management, and analyze the relationship between public perception and participation in plastic waste management. The research was conducted through explanatory research with a cross-sectional design. The population in this study is the people of Kelapa Island, Seribu Islands, DKI Jakarta with a sample of 300 respondents. The results showed that there was a relationship between knowledge (p-value = 0.001) and the role of government/community leaders (p-value = 0.002) with perceptions of plastic waste management. There is a relationship between public perception and participation in plastic waste management (p-value = 0.000). The conclusion shows that the perception of the community as a whole is positive and community participation in the management of plastic waste is already high. It is hoped that the programs that have been successfully implemented need to be maintained, improved, and monitored regularly.